Exploring the cooling effect of urban parks based on the ECOSTRESS land surface temperature - Liu, Yihui; Xu, Xinliang; Wang, Fei; Qiao, Zhi; An, Hongmin; Han, Dongrui; Luo, Jie (Frontiers in Ecology and Evolution, 2022)
Understanding the cooling effect (CE) of urban parks is vital to mitigate the urban heat islands. ECOsystem Spaceborne Thermal Radiometer Experiment on Space Station (ECOSTRESS) land surface temperature data (LST) data were used to construct diurnal thermal variations to explore the CE of urban parks in the fifth ring regions of Beijing. Local climate zone (LCZ) classification was used to distinguish different parks for examining the internal CE of parks. New subclasses of LCZ (e.g., LCZAG, LCZBG, LCZCG) were created based on the basic subclasses, such as LCZA (mainly consist of dense trees), LCZB (scattered tress with dense bush), LCZC (scattered bush), and LCZG (water). The external CE of parks was evaluated in different directions, and the impacts of buildings around parks on the external CE were also analyzed. The results showed that urban parks tended to heat up slower than the whole urban regions during the daytime, and water releasing energy dominated the mean LST of parks at night. Large parks meeting the minimum area (40,000 m2) of LCZ had better CE inside each park during the daytime. Three hundred thirty four large parks were divided into six types of LCZ. The strength of the CE decrease with the increases of distance, and seemed to exist at a distance of up to 150–200 m. Such impacts of parks were insignificant at night. In addition, parks containing certain dense trees and water had better CE inside and out. The height and density of buildings had a relatively obvious impact on the CE of parks. This study can provide insight into the impacts of urban parks on the urban thermal environment and promote the CE of urban parks in future urban planning.